Abobotulinumtoxina injections in shoulder muscles to improve adult upper limb spasticity: Results from a phase 4 real-world study and a phase 3 open-label trial - Thierry Lejeune; Svetlana Khatkova; Lynne Turner-Stokes; Philippe Picaut; Pascal Maisonobe; Jovita Balcaitiene; François Constant Boyer (Medical Journals Sweden, 2020)
Botulinum toxins, such as abobotulinumtoxinA, are used to treat spasticity (muscle overactivity) in arm muscles. Spasticity in shoulder muscles occurs in many patients following a stroke. Shoulder spasticity can be painful and limit limb movement. This paper compares the results from patients who did and those who did not receive abobotulinumtoxinA injections in shoulder muscles (among other arm muscles) in 2 studies. In both studies, the results showed that more patients receiving treatment in shoulder muscles chose pain as a key goal for treatment and had reduced pain following treatment compared with patients not treated in the shoulder. In addition, patients receiving shoulder injections showed further improvement in arm movement compared with those not receiving shoulder injections. Overall, these results suggest that abobotulinumtoxinA treatment in shoulder muscles may improve outcomes for patients with arm spasticity involving the shoulder.